2015
DOI: 10.12691/ajphr-3-3-1
|View full text |Cite
|
Sign up to set email alerts
|

University Students' Attitudes towards Genetic Testing: A Comparative Study

Abstract: Background: Genetic counseling has become a tool for preventing genetic diseases in western society.It deals with the risk of genetic diseases in families and finds ways to prevent future problems. The public's decision making regarding genetic counseling is influenced by cognitive, cultural and religious variables. Aim and objectives: To examine the attitudes of undergraduate Israeli students toward genetic issues and learn how these are affected by the field they study, their religious affiliation and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Precisely, attractiveness is aspect of genetics where atheists had a more positive attitudes to genetics then non atheists. Another similar result was possible to find in the study of Grosschedl, Konnemann & Basel (2014) or Siani & Assaraf (2015). Also Allum et al (2014) they found out that Catholics, as well as those who attend church often, were less likely to support the genetic testing of unborn babies.…”
Section: Discussionsupporting
confidence: 68%
“…Precisely, attractiveness is aspect of genetics where atheists had a more positive attitudes to genetics then non atheists. Another similar result was possible to find in the study of Grosschedl, Konnemann & Basel (2014) or Siani & Assaraf (2015). Also Allum et al (2014) they found out that Catholics, as well as those who attend church often, were less likely to support the genetic testing of unborn babies.…”
Section: Discussionsupporting
confidence: 68%
“…In Israel, differences in religious belief and custom are clearly reflected in differing genetic practices, with some sectors rejecting participation in genetic testing due to their religious beliefs (Raz 2004;Rosner et al 2009;Sher et al 2003;Zlotogora 2002). Moreover, Jewish religious students, especially those who do not study life sciences, have been found to place less trust in genetic tests than secular students do (Siani and Assaraf 2015). An understanding of the differences between various religions and the beliefs associated with them will help us understand the manner in which individuals relate to the tension between faith and science (Dickerson et al 2008).…”
Section: Religious Affiliation Among Jews As An Influencing Factormentioning
confidence: 99%
“…A previous study has also demonstrated the reluctance of young doctors to deal with matters related to genetic counselling which shows they are not only reluctant to undergo the tests but are unable to guide their patients in this regard as well. 11 On the contrary another study reports high level on interest of young physicians in genetic testing but considerable resistance regarding its clinical applicability. 13 The strength of this study is that to date genetic risk testing has not been introduced in the clinical settings in Pakistan and the reasons for this are vague.…”
Section: Discussionmentioning
confidence: 99%
“…10 Despite the encouraging response received from our study participants the level of awareness in the participants hailing from the Europe and America is significantly higher than that seen in our region. 11 The attitude of the students in undergoing a genetic risk test was much better as compared to the medical college teachers.…”
Section: Discussionmentioning
confidence: 99%